Inflation and the rate of interest - LUTZ, F.A. (PSL Quarterly Review, 2013)
Henry Thornton was the originator of two theories about the connection between inflation and the rate of interest dating back to the early 19th century and which are still discussed today. The first concerns the effect of the interest rate level on inflation. The second deals with the converse relationship, i.e. with the effect of inflation on the level of the interest rate. The present article merges these two theories into a single model. First, however, the author makes some remarks on the results of certain empirical investigations concerning the second problem, i.e. the effect of inflation on the interest rate. JEL: E31, E43